The Influence of the STEM-Based I-LVEP Model in Instilling Nationalism Character in Elementary School Students - Agustina, Shintia Dwi; Apriani, An-Nisa; Sari, Indah Perdana; Suryandari, Suryandari (Universitas Muhammadiyah Yogyakarta, 2025)
The establishment of student character is paramount in Indonesia’s teaching. The absence of strong moral principles in students can result in selfishness and ignorance toward the welfare of the country. These actions are caused by an identity crisis due to students’ weak personality, the demands of a modern lifestyle, and limited knowledge about the nationalism character. Hence, this study examined the impact of the STEM-based I-LVEP model in instilling students’ nationalism character. A quasi-experiment with an associative quantitative approach was adopted, equipped with a pretest-posttest non-equivalent control group design. The population comprised fourth-grade students at SDN Ngebel. The experimental and control groups consisted of 44 students, determined using purposive sampling. This study employed observational data. The statistical analysis utilized a t-test, with a parametric independent sample t-test, unveiling that the t-count surpassed the t-table at a significance level of 0.05. The hypothesis testing demonstrated that the STEM-based I-LVEP learning model impacted students’ nationalism character, making it an effective approach for instilling the character. It provides a noteworthy commitment in teaching students to act respectfully, appreciate differences, maintain solidarity, live in harmony, and deliver flexibility to others. These findings can serve as the basis for learning media focusing more on instilling the nationalism character since elementary school.